ACTUAL PROBLEMS OF CULTURAL POLICY OF KAZAKHSTAN - А.М.Nyssanbayeva (Scientific Journal of Pedagogy and Economics, 2021)
the cultural policy development is becoming one of the factors for maintaining not only interethnic, interconfessional tolerance, but also socio-political stability in the country. In this sense, only national cultural values are capable of withstanding the negative consequences of globalization changes, preserving the integrity of national and cultural consciousness and laying the foundation for the spiritual renewal of Kazakhstani people. The influence of global transit can lead not only to a change in the social, political, cultural systems, but also to a shift in cultural values, orientations, cultural codes in the public consciousness of the population. In this regard, the study of cultural values and orientations is of particular relevance; it can become an indicator of the state cultural policy, it allows to assess the cultural policy effectiveness, identify existing pressing problems, search for ways to solve them, make a forecast for the cultural areas development for the upcoming years. At the same time, the cultural heritage preservation of the Great Silk Road is hindered by a number of negative factors, such as an acute shortage of specialists in cultural studies, bureaucracy and insufficient funding for the architectural monuments protection. To solve them, experts propose the creation of integration zones in the Central Asian region, a single tourism cluster. During the analysis of the expert survey results, three groups of experts were identified: optimists-idealists, supporters of a full-fledged dialogue, intercultural exchange, enrichment of the cultures of the West and the East (more than 50%); materialists, supporters of the restoration of unique architectural complexes, monuments, striving for the development of the Central Asian region countries (30%) and pessimists. This may indicate a divergence of expert opinions on this issue.